MENINGKATKAN INTERAKSI SOSIAL MELALUI KEGIATAN BUDAYA RUTINAN YASIN–TAHLIL - Adam, Muhammad Rifki; Kusumadewi, Ari; Naqiyah, Najlatun (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
Social interaction is the primary foundation for creating a harmonious and cohesive society. In the context of modernization, globalization, and the development of individualistic lifestyles, as well as the intensity of social interactions within society, particularly in the field of education, religious activities and local religious practices hold a strategic role as a means to foster and strengthen social ties among members of the community. The purpose of this article is to examine the routine cultural activities of Yasin-Tahlil as a means to enhance social interaction among the residents of Jatikalang Village, Krian Subdistrict. The author of this article employs a descriptive qualitative approach, utilizing literature analysis and social analysis in relation to the practical implementation of Yasin-Tahlil activities in the community. The focus is on how these activities are conducted, how the community participates, and the existing social norms. The findings of the analysis indicate that the Yasin-Tahlil activities are more than just a means of worship. In addition to strengthening the religious and cultural identity of the community, these activities can foster social cohesion, solidarity, and brotherhood. Thus, the routine of Yasin-Tahlil makes a significant contribution to improving the quality of social interaction and strengthening the social cohesion of the Jatikalang Village community. The preservation and strengthening of such cultural-religious activities are essential for promoting social harmony and the sustainability of the community's way of life in the face of social change. ABSTRAK Interaksi sosial merupakan dasar utama untuk menciptakan masyarakat yang harmonis dan kohesif. Dalam konteks modernisasi, globalisasi, dan perkembangan gaya hidup individualistis, serta intensitas interaksi sosial di dalam masyarakat , khususnya di bidang pendidikan ,. Dalam konteks ini , kegiatan keagamaan dan keagamaan lokal memiliki peran strategis sebagai sarana untuk membina dan memperkuat ikatan sosial di antara masyarakat . Tujuan artikel ini adalah untuk meneliti kegiatan budaya rutin Yasin - Tahlil dalam rangka meningkatkan interaksi sosial di antara warga Desa Jatikalang, Kecamatan Krian. Penulis artikel ini menggunakan pendekatan kualitatif deskriptif dengan analisis literatur dan analisis sosial dalam kaitannya dengan implementasi praktis kegiatan Yasin - Tahlil di masyarakat. Fokusnya adalah pada bagaimana kegiatan tersebut dilakukan , bagaimana masyarakat berpartisipasi , dan norma - norma sosial yang ada . Temuan analisis menunjukkan bahwa kegiatan Yasin - Tahlil lebih dari sekadar​​​​​​sarana ibadah. Selain memperkuat identitas keagamaan dan budaya masyarakat , kegiatan ini dapat menumbuhkan kohesi sosial , solidaritas dan persaudaraan . Dengan demikian , rutinitas Yasin - Tahlil memberikan kontribusi yang signifikan dalam meningkatkan kualitas interaksi sosial dan memperkuat kohesi sosial masyarakat Desa Jatikalang . Pelestarian dan penguatan kegiatan budaya - keagamaan semacam ini sangat penting untuk mendorong keharmonisan sosial dan keberlanjutan cara hidup masyarakat dalam menghadapi perubahan sosial.​